Patient Satisfaction With Home Care Services Between Sibolga District, Sibolga City 2020 - Piuskosmas Fau; Devi Kristina Hutagalung; Tenti Kurniawati (Science Midwifery, 2020)
Thisre searchis base dont heimportan ceof health services for thecommunity. Home Care which is a continuous and comprehensive health serviceprovided to individuals and families in their residence has not yet found variousob staclesin the implementation.In general, this study aims to describe patient satisfaction after receivingHomecare service from Homecare Team of Puskesmas Antara. This researchuses descriptive qualitative research type. The focus of his research on patientsatisfaction. Data collection techniques are interviews, observations and also based on documents from the Home Care Puskesmas Antara.The results show the dimensions of physical evidence (tangibles), giveattention (empathy), reliability (reliability), responsiveness, assurance (assurance) related to satisfaction in this case patient satisfaction is fulfilled and the implementation of Home Care in Puskesmas Antara goes well.